Case Report: Clinical Features of a Chinese Boy With Epileptic Seizures and Intellectual Disabilities Who Carries a Truncated NUS1 Variant - Zhang, Pingli; Cui, Di; Liao, Peiyuan; Yuan, Xiang; Yang, Nuan; Zhen, Yuanyuan; Yang, Jing; Huang, Qikun (Frontiers in Pediatrics, 2021)
The mental retardation-55 with seizures (MRD55) is a rare genetic disease characterized by developmental delay, intellectual disability, language delay and multiple types of epileptic seizures. It is caused by pathogenic variants in the NUS1 gene, which encodes Nogo-B receptor (NgBR), a necessary subunit for the glycosylation reactions in mammals. To date, 25 disease-causing mutations in NUS1 have been reported, which are responsible for various diseases dystonia, Parkinson’s disease, developmental and epileptic encephalopathy as well as congenital disorder of glycosylation. In addition, only 9 of these mutations were reported with detailed clinical features. There are no reports about Chinese cases with MRD55. In this study, a novel, de novo pathogenic variant of NUS1 (c.51_54delTCTG, p.L18Tfs*31) was identified in a Chinese patient with intellectual disability and epileptic seizures. This pathogenic variant resulted in truncated NgBR proteins, which might be the cause of the clinical features of the patient. Oxcarbazepine was an effective treatment for improving speech and movement of the patient, who consequently presented with no seizure. With this novel pathogenic variant found in NUS1, we expand the genotype spectrum of MRD55 and provide valuable insights into the potential genotype-phenotype correlation.